Elements of optimizing user engagement in e-commerce website - Lizawati Rosclaritha Maidom; Aslina Baharum; Rozita Ismail; Nur Shahida Ab Fatah; Muhammad Omar; Noorsidi Aizuddin Mat Noor (Springer, 2022)
E-Commerce companies are faced with a highly competitive environment today. Strengthening and optimizing the user engagement elements in an ECommerce is a promising approach to increasing value co-creation. However, the lagged of attention to the recognition of user oriented emotional needs and expansion of user-driven demands in E-Commerce will eventually deteriorate business using the platform. Theoretical foundation of user engagement research is also still relatively underdeveloped. The purpose of this research is to explore and validate the user engagement attributes as it applies to peoples’ experiences with technology. By building the attributes that asserts the theory of engagement and recognised fundamental attributes, the reliability factorswere then assessed for validation. Preliminary study and reliability analysis were used for the identification of user engagements that would benefit E-Commerce. The result of this research reveals six attributes of user engagements and the reliability of the constructs was computed and have an alpha greater than 0.70 which presents excellent internal consistency reliability. Results indicate user engagement is a process comprised of six focused attention, perceived usability, aesthetics, endurability, novelty, and involvement. The process is characterized by attributes of engagement that pertain to the user, the system, and user-system interaction. This research provides the foundation for future work to further explore the conceptual model in various application areas, and to develop methods to measure engaging user experiences.